Seismic response of a bridge with friction pendulum isolator system - Krishnamoorthy, A. (Journal of Structural Engineering, 2025)
Numerical procedure to analyse a bridge with sliding isolator between the superstructure and pier subjected to earthquake ground motion is developed. In the analysis, superstructure, sliding bearing and pier are considered as one unit. Sliding bearing is modeled as a fictitious spring with large value of stiffness during non sliding phase and zero stiffness during sliding phase. Analysis is used to study the response of a bridge with variable friction pendulum isolator (VFPI) system. Effectiveness of the isolator is studied when the bridge is subjected to real earthquake ground motion due to El centro earthquake, Northridge earthquake and Chi Chi earthquake. In addition, effects of excitation frequency, friction coefficient and time period on response of bridge are also studied. Response of the isolated bridge with VFPI system is compared with the response of the bridge isolated with friction pendulum system (FPS). To study the effectiveness of isolation, response of the isolated bridge with FPS and VFPI system is compared with the response of the non isolated bridge. It is shown that response of the bridge reduces considerably due to isolation. Also, the performance of a VFPI system is better than the performance of a FPS isolator for a bridge subjected to earthquake ground motion.